2020
DOI: 10.1007/s42452-020-1960-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, durability and economic performance of concrete incorporating fly ash and recycled aggregates

Abstract: This paper studies the impact of replacing natural coarse aggregates (NCA) with recycled coarse aggregates (RCA) and cement (OPC) with fly ash (FA), on properties and economy of concrete. RCA was obtained by crushing old concrete specimens. FA of low calcium type was used to partially replace OPC. A total of nine concrete mixes (including a reference mix) were prepared using 50% RCA, and 100% RCA with four different levels of FA (0% FA, 10% FA, 20% FA, 30% FA). Workability, fresh density, compressive strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…has been studied widely considering the mechanical performance of the material. FA also improves the workability of RAC and reduces the requirement of water-reducing chemicals to attain the required level of flow in fresh concrete [16]. Poon et al [17] reported that the drawbacks of RAC (such as poor durability) can be minimized by the utilization of 25-35% FA as a cement substitution material.…”
Section: Introductionmentioning
confidence: 99%
“…has been studied widely considering the mechanical performance of the material. FA also improves the workability of RAC and reduces the requirement of water-reducing chemicals to attain the required level of flow in fresh concrete [16]. Poon et al [17] reported that the drawbacks of RAC (such as poor durability) can be minimized by the utilization of 25-35% FA as a cement substitution material.…”
Section: Introductionmentioning
confidence: 99%
“…It is well understood that, despite environmental and economic benefits [6,7], RC has inferior hardened properties compared to natural/normal aggregate concrete (NC). RA containing the low-density mortar is the weakest link in RC.…”
Section: Introductionmentioning
confidence: 99%
“…En las tablas VII, VIII y IX se muestran los análisis de precios unitarios para la elaboración de 1 m 3 de tres tipos de concretos: NTC-0, NTC-0.15 y con cenizas volantes para un 30% de adición (CV-30), habiéndose escogido la CV por sus propiedades puzolánicas similares al NTC. Para los dos primeros, los precios unitarios se obtuvieron de [33] y en el NTC-0.15 se incluyó el transporte de 1 Kg de NTC desde Nanjing-China a Lima-Perú por el importe de $49.92 USD; y para el tercero los precios se obtuvieron de [34]. En las Tablas mencionadas se observa que los costos unitarios totales para 1 m 3 [35], realiza el estudio del asentamiento de dos mezclas de concreto con NTC y una mezcla de concreto convencional (0%), empleando las cantidades de 0.3% de adición de NTC con dispersión y 0.3% sin dispersión.…”
Section: Valoración Económicaunclassified
“…Son escasas las investigaciones en el campo económico sobre la utilización de los NTC en la fabricación del concreto, la Ref. [34] estudia el reemplazo del cemento por cenizas volantes (CV) y por NTC, para evaluar su costo/resistencia con respecto al NTC-0; encontrando que con 30% de CV se reduce el costo total del concreto en más del 15% y que el concreto con NTC es más caro, ambos, que el concreto con NTC-0.…”
Section: Introductionunclassified